Urban Chronology at a Human Scale on the Coast of East Africa in the 1st Millennium a.d. (2nd January 2021) - Wynne-Jones, Stephanie; Sulas, Federica; Out, Welmoed A.; Kristiansen, Søren Munch; Fitton, Tom; Ali, Abdallah K.; Olsen, Jesper
ABSTRACT: This paper presents a new high-resolution excavation sequence of a house at the 1st millennium a.d. site of Unguja Ukuu, Zanzibar, with implications for a new and detailed understanding of the period between the 7th and 9th centuries a.d. on the East African coast. This is an important period associated with a broad and distinctive cultural tradition, often seen as a pre- or proto-urban phase. Household excavations at Unguja Ukuu revealed two occupation phases, spanning less than 40 years each. The results here thus present an unprecedented temporal resolution on the site, at the scale of human experience. Excavation and microstratigraphic analyses of multiple floor layers reveal decadal change in occupation at this house. Positioning this house into the broader settlement sequence, we argue for episodic settlement at the site of Unguja Ukuu and draw out detail on how we can explore change at this generational scale.